ANALISIS PENGARUH PERTUMBUHAN EKONOMI PENGELUARAN PEMERINTAH NILAI TUKAR TERHADAP INFLASI DI INDONESIA - Nugraha, Fachri; Khoirudin, Rifki (Journal Economics Technology And Entrepreneur, 2024)
This research was conducted to analyze the effect of economic growth on government expenditure on exchange rates on inflation in Indonesia. The research method uses descriptive analysis with the VECM (Vector Error Correction Model) analysis method. The unit of analysis in this research is the country, with data obtained from one country, namely Indonesia. The time horizon used in this research is a time series, with data collection carried out monthly, starting from 1990 to 2022. The results of this research produce variables of economic growth, government spending, exchange rates which have a significant effect in the long term. In the short term, economic growth, government spending and interest rates have no effect. Meanwhile, the money supply variable has no effect in the long term or short term.